Ecofriendly synthesis and solar photocatalytic activity of S-doped ZnO - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Hazardous Materials, 2010)
The S-doped ZnO was prepared by new ecofriendly method, which involves simple mechanochemical synthesis followed by thermal decomposition of bisthiourea zinc oxalate (BTZO) powders. The BTZO was characterized by FTIR and TG-DTA analysis while S-doped ZnO crystallite was characterized by XRD, XPS, SEM, EDXS, and photoluminescence (PL) spectra. X-ray diffraction data suggest the single phase wurtzite structure for S-doped ZnO and the incorporation of sulfur expand the lattice constants of ZnO. Room temperature PL spectra show more number of oxygen vacancies in S-doped ZnO as compare to that of pure ZnO. Photocatalytic activity of S-doped ZnO was checked by means of solar photocatalytic degradation (PCD) of resorcinol, using a batch photoreactor. The PCD efficiency of S-doped ZnO was found to be 2 times greater than that of pure ZnO. The inherent relationship between PL intensity and photocatalytic activity of S-doped ZnO was discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Photocatalysis; photoluminescence; Resorcinol; S-doped ZnO; Sunlight; XPS

Enhancement of oxygen vacancies and solar photocatalytic activity of zinc oxide by incorporation of nonmetal - Patil, Ashokrao B.; Patil, Kashinath R.; Pardeshi, Satish K. (Journal of Solid State Chemistry, 2011)
B-doped ZnO and N-doped ZnO powders have been synthesized by mechanochemical method and characterized by TG-DTA, XRD, SEM-EDX, XPS, UV-visible and photoluminescence (PL) spectra. X-ray diffraction data suggests the hexagonal wurtzite structure for modified ZnO crystallites and the incorporation of nonmetal expands the lattice constants of ZnO. The room temperature PL spectra suggest more number of oxygen vacancies exist in nonmetal-doped ZnO than that of undoped zinc oxide. XPS analysis shows the substitution of some of the O atoms of ZnO by nonmetal atoms. Solar photocatalytic activity of B-doped ZnO, N-doped ZnO and undoped ZnO was compared by means of oxidative photocatalytic degradation (PCD) of Bisphenol A (BPA). B-doped ZnO showed better solar PCD efficiency as compare to N-doped ZnO and undoped ZnO. The PCD of BPA follows first order reaction kinetics. The detail mechanism of PCD of Bisphenol A was proposed with the identification of intermediates such as hydroquinone, benzene-1,2,4-triol and 4-(2-hydroxypropan-2-yl) phenol. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Bisphenol A; Enhanced oxygen vacancies; Nonmetal doping; Photocatalysis; Sunlight

Spin transport and magnetic correlation parameters for graphene-like nanocarbon sheets doped with nitrogen - Alegaonkar, Ashwini P.; Kumar, Arvind; Patil, Sagar H.; Patil, Kashinath R.; Pardeshi, Satish K.; Alegaonkar, Prashant S. (Journal of Physical Chemistry C, 2013)
Globally, graphene magnetism has captivated the attention of researchers in recent years. To obtain magnetic ordering, irregularities in the carbon network, like defects, adatoms, etc., are essential. Herein, we report on spin transport and magnetic correlations in graphene-like nanocarbon sheets (GNCs) that were doped with nitrogen by use of tetrakis(dimethylamino)ethylene (TDAE). The spin transport measurements, performed by electron spin resonance technique, showed that both spin-spin and spin-lattice relaxation times are increased by nitrogen doping. The magnetic correlations, measured on a vibrating sample magnetometer, showed that ordering parameters are reduced for nitrogen-loaded GNCs. Chemical analysis, carried out via electron spectroscopy, revealed that nitrogen atoms exchange couples electron-to-hole with the carbon network Analysis of I-V measurements showed that higher-order resistance is appreciably decreased for nitrogen-doped GNCs. The observed decrease is due to an increase in nonbonding states baying small local density. After doping, states in this region may be localized pi spin populated around the doped region. By and large, the approximately 20% magnetization that exists in GNCs is found to be reduced to 5% by introduction of nitrogen.

Crystal structure, computational studies, and stereoselectivity in the synthesis of 2-aryl-thiazolidine-4-carboxylic acids via insitu imine intermediate - Jagtap, Rohidas M.; Rizvi, Masood A.; Dangat, Yuvraj B.; Pardeshi, Satish K. (Journal of Sulfur Chemistry, 2016)
This article presents the synthesis of (2R/2S,4R)-2-aryl-thiazolidine-4-carboxylic acids via nucleophilic addition of L-Cysteine on aromatic aldehydes involving a yield and time-effective room temperature reaction in an aqueous DMSO medium in the presence of NaHCO3 as a base. The synthesized diastereomers were spectroscopically characterized and quantified for diastereomeric excess by liquid chromatography-mass spectrometry analysis. The impact of the type and position of substituent in aromatic aldehydes on reaction time, % yield, H-1 NMR shift at newly formed chiral center [C(2)-H], and diastereomeric excess (de%) have been investigated. A plausible mechanism for stereoselectivity via an in situ imine intermediate is proposed using real-time IR monitoring of the synthetic reaction based on the significant signals at 1597, 1593cm(-1) for imine (C=N) stretching. The imine mechanism for stereoselectivity was further supported by NMR studies of azomethine C-13 NMR signals at 159, 160ppm and by the single crystal structure of hitherto unknown (2S,4R)-3-(tert-butoxycarbonyl)-2-(2-hydroxyphenyl)thiazolidine-4-carbox ylic acid (3a) obtained as a major diastereomer in the synthesis of the butyloxy carbonyl (BOC) derivative of (2R/2S,4R)-2-(2-hydroxyphenyl)thiazolidine-4-carboxylic acid. The significant ortho-OH effect of phenolic hydroxyl group leading to strong hydrogen bondings plays a vital role in the formation of 2S,4R BOC derivative stereoselectively. The frontier molecular orbitals, possible electronic excitations, IR band characterizations, and reactivity parameters of newly reported compound (3a) have been predicted using quantum chemical descriptors from density functional theory. The theoretical exploration of experimental spectra using time-dependent DFT indicated a (-*) transition between HOMO and LUMO in the ultraviolet region.
Keywords: 2-aryl-thiazolidine-4-carboxylic acids; density function theory; frontier molecular orbitals; imine intermediate; X-ray crystal structure

X-ray crystal structures and anti-breast cancer property of 3-tert-butoxycarbonyl-2-arylthiazolidine-4-carboxylic acids - Jagtap, Rohidas M.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Khan, Ayesha A.; Pardeshi, Satish K. (New Journal of Chemistry, 2018)
Diastereomeric `2RS, 4R'-2-arylthiazolidine-4-carboxylic acids (ATCAs) were synthesized and their resolution to chiraly pure N-BOC derivatives was attempted by column chromatography. The absolute stereochemistry of the resolved compounds was ascertained by X-ray single crystal structures. Further application of the synthesized compounds was studied for their in vitro anti-breast cancer activity against MCF7 cell line using DOX as a standard by MTT assay method. Cell morphology analysis was carried out by fluorescence microscopy. The compounds containing `2S' absolute configuration in thiazolidine ring and presence of 2-NO2, 2,6-Cl groups on `2R'-aryl substituent showed significant antibreast cancer activity where some of the compounds were found to be more active than DOX in terms of induced apoptosis mode of MCF7 cell death.

Cyanuric-chloride-mediated synthesis of 2-Aryl-3-tert-butoxycarbonyl-thiazolidine-4-carboxylic acid anilides: mechanistic, X-ray crystal structures and cytotoxicity studies - Jagtap, Rohidas M.; Shaikh, Samir R.; Gonnade, Rajesh G.; Raheem, Shabnam; Rizvi, Masood A.; Pardeshi, Satish K. (ChemistrySelect, 2019)
The `2R,4R'-2-aryl thiazolidine-4-carboxylic acid anilides (ATCAAs) were synthesized using cyanuric chloride (CC) as a clean and substoichiometric acid-amine coupling agent under optimized reaction conditions. The diesterphenol intermediate based mechanism is proposed and supported by spectral characterization of the intermediate. The single crystal X-ray structures of acid substrate (2R,4R)-3-(tert-butoxycarbonyl)-2-(2-methoxyphenyl)thiazolidine-4-carbox ylic acid (3 a) and anilides (R)-tert-butyl 4-(2-fluorophenylcarbamoyl)thiazolidine-3-carboxylate (4 b), (2R,4R)-tert-butyl 2-(2,6-dichlorophenyl)-4-(m-tolylcarbamoyl)thiazolidine-3-carboxylate (6 b) confirmed the formation of chiral anilides. The synthesized library of anilides [(R)-tert-butyl 4-Aryl thiazolidine-3-carboxylate and (2R,4R)-tert-butyl 2-Aryl-4-Aryl thiazolidine-3-carboxylate] 4 a-6 f was screened for their in vitro anti cancer, neuronal and neuroprotective studies. The anilides 4 b, 4 g, 5 d, 5 h, 6 c and 6 f (where the aryl=2-fluorophenylcarbamoyl, 4-chlorophenylcarbamoyl, 2-methoxyphenyl, 2,5-dichlorophenylcarbamoyl, 2,6-dichlorophenyl, 4-chlorophenylcarbamoyl respectively)were found to be less cytotoxic towards N2 A, SHSY-5Y neuronal cell lines in their differentiated and undifferentiated forms, and also exhibited dose dependant anti-inflammatory properties for a possible identification towards neurodegenerative and inflammatory disorders.
Keywords: Acid-amine coupling; Cyanuric chloride; Cytotoxicity; Mechanistic investigations; Single crystal x-ray structure

Pyridazine-Based Aggregation Induced Emission Active Conjugates: Synthesis, Single Crystal XRD Analysis, and Self-Assembly Assessment - Waghchoure, Aishwarya P.; Sangale, Vijay B.; Shaligram, Parth S.; Lambud, Sushil; Pardeshi, Satish K.; Gonnade, Rajesh G.; Bandaru, Sateesh; More, Sandeep; Reddy, J. Prakasha; Bhosale, Rajesh S. (CHEMISTRYSELECT, 2024)
Keywords: AIE; Pyridazine; Self-assembly; Single crystal